Karakter Fisikokimia Buah Melon Cantaloupe (Cucumis melo L. var. Cantaloupe) yang Dipanen Awal: Physicochemical Characteristics of Early Harvested Cantaloupe Melon (Cucumis melo L. var. Cantaloupe) - Nidya Putri Zulia Kusuma Wardani; Suketi, Ketty; Arif, Abdullah Bin (Jurnal Hortikultura Indonesia, 2025)
Cantaloupe (Cucumis melo L var. Cantaloupe) is a climacteric fruit that shows rapid physical and morphological changes after the fruit is harvested. The shelf life of the fruit can be extended by harvesting early after the fruit has reached the physiological ripeness stage. This study aimed to assess the effect of early harvesting time on the quality of cantaloupe fruit during storage. The experiment was conducted at the Research Center for Tropical Horticulture, Bogor Agricultural University (PKHT, IPB) Farm Tajur, Bogor, and postharvest ripening test was conducted at Postharvest Laboratory, Department of Agronomy and Horticulture, Bogor Agricultural University. Parameters observed included respiration rate, ethylene production, changes in skin wrinkling, soluble sugar concentration (SSC), titratable acidity (TA), and vitamin C content. The result showed that cantaloupe harvested early at 32 days after anthesis has peak respiration at 7 days after harvest, peak ethylene production 9 days after harvest, shrivel incidence of the fruit skin at 18 days after harvest, highest PTT content (6.99 oBrix), ATT (0.02 mL g-1), PTT/ATT ratio (493.75), and vitamin C content (20.65 mg (100 g)-1. Keywords: climacteric fruit, postharvest quality, shelf life, ethylene production